Depth structure and hydrocarbon potential of the middle part of the northwestern Black Sea shelf, according to density modeling - Kozlenko, M.V.; Kozlenko, Yu.V. (Geofizicheskiy Zhurnal, 2025)
Considering the need to ensure Ukraine’s energy independence after the war, it is expedient to identify in advance the structures suitable for extracting hydrocarbon materials in the currently inaccessible region of the northwestern shelf of the Black Sea. To do this, gravity modeling was carried out using a network of submeridional profiles, which made it possible to determine the deep structure and fault tectonics. Based on the calculations, the prospects of exploring the research area for hydrocarbon deposits were determined.